2015
DOI: 10.1021/acsnano.5b01634
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of a Plasmonic Molecule

Abstract: Photoluminescent Au nanoparticles are appealing for biosensing and bioimaging applications because of their non-photobleaching and non-photoblinking emission. The mechanism of one-photon photoluminescence from plasmonic nanostructures is still heavily debated though. Here, we report on the one-photon photoluminescence of strongly coupled 50 nm Au nanosphere dimers, the simplest plasmonic molecule.We observe emission from coupled plasmonic modes as revealed by single-particle photoluminescence spectra in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
116
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 52 publications
3
116
2
Order By: Relevance
“…51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 stabilized 50 nm Au colloids (BBI Solutions) were washed with Millipore filtered deionized water and concentrated 10 times by centrifugation at 1400 rcf for 5 min. 200 µL of acetonitrile was added to the suspension and stirred for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 stabilized 50 nm Au colloids (BBI Solutions) were washed with Millipore filtered deionized water and concentrated 10 times by centrifugation at 1400 rcf for 5 min. 200 µL of acetonitrile was added to the suspension and stirred for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…TEM analysis showed that the resulting solution contained 23% dimers with gap widths ranging from 1 to 5 nm. 51 Au Film Preparation: Semi-transparent conductive thin films were fabricated on clean glass coverslips by electron-beam evaporation of a 2 nm Ti adhesion layer followed by a 20 nm Au thin film. Film thickness was measured during deposition using a quartz crystal microbalance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing the interparticle distance leads to a redshift of the scattering spectra and a correlated redshift of the PL spectra (Figure 3b). Nevertheless, the PL is slightly blueshifted with respect to the scattering spectrum 10,15,24,25,30 except for the closest distance. Most interestingly, the PL intensity is significantly decreased for decreasing distances d ; this is in contrast to the scattering intensity, which increases with decreasing d .…”
mentioning
confidence: 90%
“…8 Further, it was recognized that a redshift of the scattering spectrum (due to gradual changes in geometry of gold nanostructures) is associated with a decrease of the PL intensity, while the scattering intensity increases 15,25,33 and while the absorption strength remains largely unchanged. 30 Only recently, it was pointed out by Lumdee et al 32 and Andersen et al 33 (following original ideas from Boyd et al 3 ) that the PL yield should follow the integral of the electric field squared inside the gold nanostructures as well as the gold-intrinsic d-hole recombination rate rather than scattering strengths or hot-spot intensities. However, their experiments were restricted to a single distance between a localized particle plasmon and a thin film surface plasmon.…”
mentioning
confidence: 99%